2020
DOI: 10.1093/ije/dyaa169
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality during the COVID-19 outbreak in Italy: a two-stage interrupted time-series analysis

Abstract: Background Italy was the first country outside China to experience the impact of the COVID-19 pandemic, which resulted in a significant health burden. This study presents an analysis of the excess mortality across the 107 Italian provinces, stratified by sex, age group and period of the outbreak. Methods The analysis was performed using a two-stage interrupted time-series design using daily mortality data for the period Janua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 16 publications
7
112
1
3
Order By: Relevance
“…Among them, 33 (73%) were under treatment for hypertension, 23 (51%) presented neurological diseases, 19 (43%) had a chronic kidney failure and 11 (24%) assumed drugs for psychiatric disorders. The overall mortality rate was 26.67%, in line with that reported according to the median age of Italy [ 16 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Among them, 33 (73%) were under treatment for hypertension, 23 (51%) presented neurological diseases, 19 (43%) had a chronic kidney failure and 11 (24%) assumed drugs for psychiatric disorders. The overall mortality rate was 26.67%, in line with that reported according to the median age of Italy [ 16 ].…”
Section: Resultssupporting
confidence: 87%
“…To this end, we evaluated the difference in iron to ferritin ratio (IFR) as a surrogate marker of inflammation. Indeed, the increase of ferritin uncoupled from an iron increase (or in the presence of low iron values) leads to low IFR values and is usually associated with chronic inflammation [ 15 , 16 ]. Of note, we observed that the difference in IFR significantly segregates recovered and dead patients (high IFR better prognosis) in the intermediate-risk group (p: 0.012) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The highly infectious coronavirus disease 2019 (COVID-19), which is caused by a novel coronavirus, SARS-CoV-2, has evolved to be a worldwide pandemic. Italy was one of the European countries which was hardest hit by the pandemic in the spring of 2020 [ 1 , 2 , 3 ]. In the 3 months from 15 February to 15 May 2020, an average excess mortality of 29.5% was registered for the whole country, with a rate of 400% in the northern provinces, which were the most severely affected by the pandemic [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such a spatial concentration of economic activities involves the industrial manufacturing sectors to the largest extent, and the consequent high level of emissions is at least in part responsible for heavy pollution in the region [26]. During the COVID-19 pandemic, Italy has been one of the worst countries affected by the spreading of coronavirus, especially the northern regions [27].…”
Section: Study Areamentioning
confidence: 99%